Avacincaptad pegol, the second approved aptamer medicine – A mini review - Bege, Miklós; Ghanem Kattoub, Rasha; Borbás, Anikó (De Remediis, 2025)
Therapeutic oligonucleotides are employed in the treatment of a variety of diseases, primarily functioning through mechanisms associated with gene silencing technologies. In contrast, aptamers exhibit mechanisms of action that are more akin to those of protein-based monoclonal antibodies. However, owing to their oligonucleotide structure, aptamers possess several advantages over antibodies. Despite these benefits, the adoption of aptamers in clinical medicine has not reached the levels observed with monoclonal antibodies or gene-silencing oligonucleotides. Almost two decades after the approval of pegaptanib, the first approved aptameric therapeutic for the treatment of neovascular AMD (age-related macular degeneration), a second aptamer has recently received approval to treat geographic atrophy, an advanced form of AMD. In this review, we aim to provide an overview of the pharmacology and chemistry of avacincaptad pegol, the second approved aptameric drug.